The Islamic State of Indonesia (NII) and the Legacy of Kartosoewiryo: A Historical and Contemporary Political Analysis - Faisal Riza (Warisan: Journal of History and Cultural Heritage, 2024)
The proclamation of the Islamic State of Indonesia (Negara Islam Indonesia, NII) by Sekarmadji Maridjan Kartosoewiryo marked a pivotal moment in Indonesia’s political and religious landscape. This study delves into the historical development of NII, the ideological underpinnings of Kartosoewiryo’s movement, and the contemporary political ramifications of his legacy. It investigates the extent to which Kartosoewiryo’s vision continues to resonate within modern Islamist movements in Indonesia and how the historical narrative of NII has been reinterpreted in contemporary political discourse. Employing a historical-political analysis, this study draws upon primary and secondary sources, including archival records, academic studies, and contemporary reports. The findings reveal that although Kartosoewiryo’s aspiration for an Islamic state was ultimately dismantled, his ideological influence persists through various Islamist movements, shaping ongoing debates on Islam and governance in Indonesia. This study contends that Kartosoewiryo’s legacy is not merely a historical artifact but remains an active site of ideological contestation in Indonesia’s contemporary political arena. Understanding this legacy offers crucial insights into the evolution of political Islam in Indonesia and the persistent complexities surrounding the relationship between religion and the state.